19.0k views
0 votes

4m {}^(2)= 3


User DNR
by
5.7k points

1 Answer

1 vote

Answer:


m=-(\sqrt3)/(2)\ and\ m=(\sqrt3)/(2)

Explanation:

Given:

The equation given to solve is:


4m^2=3

First, we divide both sides by 4. This gives,


(4m^2)/(4)=(3)/(4)\\\\m^2=(3)/(4)

Now, we take square root on both sides. This gives,


√(m^2)=\pm\sqrt{(3)/(4)}

We know that from the definition of square root function that:


√(x^2)=x


\sqrt{(x)/(y)}=(√(x))/(√(y))

Therefore,


√(m^2)=m


\sqrt{(3)/(4)}=(√(3))/(√(4))=(\sqrt3)/(2)


m=\pm(\sqrt3)/(2)

Hence, two values of 'm' are possible. They are:


m=-(\sqrt3)/(2)\ and\ m=(\sqrt3)/(2)

User Roomcayz
by
4.7k points